Ameliorative Effect of Vitamin C and N-Acetyl cysteine on Mercury chloride-induced Neurotoxicity in Male Wistar Rats (African Journal of Biomedical Research, 2024)
The present study investigated the ameliorative effects of Vitamin C (Vit. C) and N-acetylcysteine (NAC) on mercury chloride (HgCl2)-induced neurotoxicity in male Wistar rats. Twenty (20) male Wistar rats were randomly grouped into four, n=5. I: control, received 0.5mL normal saline, II: received HgCl2 alone (5mg/kg), III: received HgCl2 (5mg/kg) plus Vit. C (100 mg/kg), IV: received HgCl2 (5mg/kg) and N-acetylcysteine (NAC) (50mg/kg) for fourteen (14) days. All the drugs were administered orally. The rats were subjected to behavioural tests (Morris water maze, novel object recognition, light and dark box, fore limb grip strength and beam walking balance tests). The rats were then euthanized to obtain brain tissues for the determination of catalase activity, total protein and nitric oxide (NO) levels. The result revealed a significant (P